indPOtrace: Digital Innovation for Smart Pig Farming and Safe Pork Supply Chains in India - Thomas, R; Bharadwaj, D; Kerketta, A; Sharma, D; Das, H; Gupta, V K (Journal of Meat Science, 2026)
The development of indPOtrace (Indian Pork Traceability platform)  marks a significant advancement in digital infrastructure for India’s  pork sector, offering a multifaceted software solution tailored to the  operational, regulatory, and advisory needs of diverse stakeholders. The  platform integrates distinct modules for end-to-end traceability, real time remote meat inspection, and interactive stakeholder engagement,  encompassing pig producers, pork processors, traders, feed suppliers,  and transporters. It enables systematic documentation of pig production  and management data, including health records and farm-specific  parameters, within a centralized database managed by ICAR-National  Research Centre on Pig. A core innovation of indPOtrace is its remote  meat inspection system trhough Meat Spec 1.0, which facilitates  real-time veterinary assessment of slaughter pigs (ante-mortem) and  carcasses (post-mortem) in operational abattoirs via virtual inspection  protocols. The platform also houses the Opti-PigRation 1.0 module,  an intelligent feed formulation tool designed to optimize the energy to-protein ratio in pig diets by farmers themselvs, particularly those  incorporating unconventional feed resources. Based on Bureau of  Indian Standards nutritional recommendations, the tool generates  precision-guided feed suggestions for improved productivity and cost efficiency. Complementing its producer-centric features, the platform  includes a consumer-facing portal enabling QR code-based traceability  of pork products, fostering consumer confidence through transparent  provenance data. indPOtrace thus represents a comprehensive, scalable,  and intelligent system driving traceable, safe, and sustainable pork  production in India.
Keywords: Pork; traceability; farm records; meat inspection; ration balancing